2016
DOI: 10.3855/jidc.7301
|View full text |Cite
|
Sign up to set email alerts
|

Reflex threshold of signal-to-cut-off ratios of the Elecsys anti-HCV II assay for hepatitis C virus infection

Abstract: Introduction: Fast screening tests for hepatitis C virus (HCV) antibody often give false-positive results. Signal-to-cut-off (S/Co) ratios were suggested to be used as reflex confirmation of anti-HCV. The Elecsys Anti-HCV II assay is an effective test for the detection of hepatitis C, but no S/Co cutoff has been reported. The aim of this study was to determine the S/Co ratio threshold of anti-HCV test using Elecsys Anti-HCV II screening and supplemental recombinant immunoblot assay (RIBA) test results as the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…CDC guidelines have recommended that the anti‐HCV threshold S/CO ratio can be used to reduce the necessity for supplemental testing and may provide additional insight into a subject's true anti‐HCV antibody status . Several previous studies have reported the threshold S/CO ratio, which predicts positive results in ≥ 95% of supplemental tests for a variety of anti‐HCV assays . Among the 181 samples with anti‐HCV CLIA‐positive results according to at least one assay, the percentages of samples with an S/CO ratio between 1.0 and 10.0 according to the Mindray anti‐HCV, Architect anti‐HCV and Elecsys anti‐HCV II assays were 14.9% (27/181), 60.7% (110/181), and 1.1% (2/181), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CDC guidelines have recommended that the anti‐HCV threshold S/CO ratio can be used to reduce the necessity for supplemental testing and may provide additional insight into a subject's true anti‐HCV antibody status . Several previous studies have reported the threshold S/CO ratio, which predicts positive results in ≥ 95% of supplemental tests for a variety of anti‐HCV assays . Among the 181 samples with anti‐HCV CLIA‐positive results according to at least one assay, the percentages of samples with an S/CO ratio between 1.0 and 10.0 according to the Mindray anti‐HCV, Architect anti‐HCV and Elecsys anti‐HCV II assays were 14.9% (27/181), 60.7% (110/181), and 1.1% (2/181), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…RIBA is labor‐intensive and time‐consuming and is no longer recommended as a supplemental test for anti‐HCV confirmation in the 2013 CDC guidelines, and only NAT is required . RIBA is still commonly used due to its high specificity in other countries, including China . In the present study, we used RIBA to analyze 181 samples with at least one anti‐HCV CLIA‐reactive result.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[25,26] Recent studies have shown that a Elecsys Anti-HCV II S/CO ratio within 12.27 to 19.0 is predictive of a true positive result in ≥95% of the cases. [27,28]…”
Section: Discussionmentioning
confidence: 99%